Legal Protection for Users of Land Deed Official (PPAT) Services Regarding Electronic Certificate Checks that Error in the Application - Febita Annisa, Shoffyah; Widayati, Widayati (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze the form of legal protection for the public if an error occurs in checking electronic certificates, as well as to examine the responsibility of PPAT in providing legal certainty. The research method used is normative legal research with a statute approach and a conceptual approach. Data sources were obtained through a literature review covering legislation, agrarian law literature, and legal doctrines related to legal protection and the authority of PPATs. The research results show that errors in checking electronic certificates can hinder the deed creation process and cause losses to the parties. In this case, legal protection can be provided in the form of preventive protection, namely through improving regulations and issuing technical instructions by the Ministry of ATR/BPN, as well as repressive protection through civil lawsuit mechanisms and administrative complaints against negligent PPAT. PPAT is obliged to act carefully, cautiously, and prioritize the principle of legal certainty in every deed creation. Therefore, the electronic land registration system requires comprehensive regulatory support, strict supervision, and increased PPAT competence to ensure legal protection for service users is truly guaranteed.